Natural Environments and Leisure among Rural–to–Urban Immigrants: An Application of Bourdieu's Concepts of Habitus, Social and Cultural Capital, and Field. (4th July 2019) - Horolets, Anna; Stodolska, Monika; Peters, Karin
ABSTRACT: This study explored the use of natural environments for leisure among rural-to-urban immigrants by adopting Bourdieu's concepts of habitus, social and cultural capital, and field. Data were collected with the use of individual interviews with 27 participants, including Mexican immigrants in the United States, Ukrainian immigrants in Poland, Moroccan immigrants in the Netherlands, and Turkish immigrants in Germany. The findings showed that for some immigrants, practices of social capital maintenance became disconnected from recreation in natural environments, while for all participants, nature-related cultural capital had low transferability in a migratory situation. Depending on their position in a new social field, immigrants developed different strategies to use local natural environments for leisure. Some strategies contributed to preserving old habitus, while one strategy (finding substitutes) contributed to gradual changes in immigrants' nature-related habitus. We suggest that embodied and emplaced skills of using nature should be incorporated in the notion of cultural capital.